Water-food-energy nexus for transboundary cooperation in Eastern Africa. Issue 4 (3rd January 2022) - Elsayed, Hamdy; Djordjevic, Slobodan; Savic, Dragan; Tsoukalas, Ioannis; Makropoulos, Christos
Abstract: Establishing cooperation in transboundary rivers is challenging especially with the weak or non-existent river basin institutions. A nexus-based approach is developed to explore cooperation opportunities in transboundary river basins while considering system operation and coordination under uncertain hydrologic river regimes. The proposed approach is applied to the Nile river basin with a special focus on the Grand Ethiopian Renaissance Dam (GERD), assuming two possible governance positions: with or without cooperation. A cooperation mechanism is developed to allocate additional releases from the GERD when necessary, while a unilateral position assumes that the GERD is operated to maximize hydropower generation regardless of downstream users' needs. The GERD operation modes were analysed considering operation of downstream reservoirs and varying demands in Egypt. Results show that average basin-wide hydropower generation is likely to increase by about 547 GWh/year (1%) if cooperation is adopted when compared to the unilateral position. In Sudan, hydropower generation and water supply are expected to enhance in the unilateral position and would improve further with cooperation. Furthermore, elevated low flows by the GERD are likely to improve the WFE nexus outcomes in Egypt under full cooperation governance scenario with a small reduction in GERD hydropower generation (2, 000 GWh/year (19%)). HIGHLIGHTS: Water-Food-Energy Nexus framework is applied to explore cooperation opportunities in shared rivers. Cooperation is likely to increase total average hydropower generation compared to the unilateral mode. Downstream drought-related risks could be reduced with negligible impacts on upstream objectives if countries agree to share the risk. A high level of coordination among countries is required to achieve the cooperation benefits.